2008
DOI: 10.1186/1475-925x-7-19
|View full text |Cite
|
Sign up to set email alerts
|

An in vitro assay of collagen fiber alignment by acupuncture needle rotation

Abstract: Background: During traditional acupuncture therapy, soft tissues attach to and wind around the acupuncture needle. To study this phenomenon in a controlled and quantitative setting, we performed acupuncture needling in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…The research group led by Langevin believes that the acupuncture effect may be explained as that the manipulation of lifting, thrusting, and twisting the needle inserted into the acupoint causes the nearby collagen fibers to be twisted and wound, by way of which the mechanical force signals pass on to the connective tissue cells and even spread further [9, 1921]. As observed by Julias et al [22], the manipulation of twisting the needle led to different extents of parallelism of the collagen fiber bundles. It is believed that the force signals pass on to the connective tissue cells via the deformation of the collagen fibers in the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The research group led by Langevin believes that the acupuncture effect may be explained as that the manipulation of lifting, thrusting, and twisting the needle inserted into the acupoint causes the nearby collagen fibers to be twisted and wound, by way of which the mechanical force signals pass on to the connective tissue cells and even spread further [9, 1921]. As observed by Julias et al [22], the manipulation of twisting the needle led to different extents of parallelism of the collagen fiber bundles. It is believed that the force signals pass on to the connective tissue cells via the deformation of the collagen fibers in the extracellular matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 7 shows the relationship between dissipation factor and frequency. It showed that Q −1 (dots in Figure 7) decreases quickly under low frequency (1)(2)(3)(4)(5)(6)(7)(8) and tends to be a steady value under high frequency. The calculating results were fitting by an exponential form function Q −1 = e −0.3ω + 0.0012 (black line in Figure 7).…”
Section: Angle Displacement Amplitude (U) Distributionmentioning
confidence: 98%
“…1 They further found fibroblast cytoskeletal remodeling induced by acupuncture. 6,7 Afterwards, Julias et al designed an in vitro quantitative setting; they verified that the mechanostructural properties of soft connective tissues may affect their response to acupuncture therapy 8 and the anatomy at acupoints provides unique boundaries that accentuate the mechanical response to needle manipulation. 9 The absence of scientific background of acupuncture mechanisms has motivated mathematicians to carry out modeling and numerical simulation of the acupuncture process from both macroscopic and microscopic aspects.…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, research showed that collagen gels have tearing after significant rotations. 15 The exact number of rotations necessary for tearing is dependent on gel density, the existence of cross-linkage, and the depth of the needle. The researchers found that gels filled with thicker densities of collagen failed at fewer revolutions than thinner gels.…”
Section: The Impact Of Needle Manipulation On Tissue Graspmentioning
confidence: 99%